Changes Of Perceived Self Esteem Dimension Using Archery As A Weekly Exercise Regime In Sedentary Youth - Mohd Azrul Anuar Zolkafi,; Norsham Juliana,; Noor Aien Mon Sarip,; Sahar Azmani,; Abd Rahman Hayati, (Elsevier, 2024)
European Journal of Molecular & Clinical Medicine, 2020, Volume 7, Issue 2, Pages 5928-5935